An?lise de desempenho do GFDM e WHT-GFDM em canais seletivos em frequ?ncia - Alves, Bruno Moreira (2014)
Cognitive Radio (CR) networks are able to establish communication using vacant channels reserved for primary users without interfering in the communication of the incumbents. In order to achieve this goal, CR must reduce out-of-band transmissions to avoid interference in adjacent channels. Usually, broadband digital communication standards that employ Cognitive engines for opportunistic spectrum allocation use Orthogonal Frequency Division Multiplexing (OFDM) as aerial interface. However, a technique called General Frequency Division Multiplexing (GFDM) has spectral characteristics that are more suitable for CR networks. The aim of this paper is to evaluate the performance of this technique under frequency-selective channels, compare it with OFDM and to evaluate the performance of this technique combined with the Walsh-Hadammard Transformation (WHT). This comparison is made considering that GFDM and OFDM symbols has the same subcarrier separation. The simulation results shows that OFDM and GFDM achieves equivalent performance under selective channels and the equations used to evaluate the performance of OFDM system can also be used to analyze the GFDM performance over frequency-selective channel. In the case associated to WHT, the advantages of WHT-OFDM can also be observed in WHT-GFDM.